A greenhouse study on ground beetle movement and predation rate based on habitat type - Cox, Elijah; Kim, Tania (My University, 2022)
Ground beetles (Coleoptera: Carabidae) are important in agro-ecosystems as generalist predators of invertebrate pests and weed seeds. However, less is known about ground beetles’ cross-over and predation rates between crop fields and grass habitats. This project seeks to identify how ground beetles move between agricultural crops and perennial grass habitats and what ground beetle predation rates are like in these habitats. We created greenhouse environments that mimic these habitats using corn, soybean, and a grass-perennial plant mix. We made planted trays of monocultures and pairwise mixtures of each plant type (6 treatments in total). Ground beetles were collected in grass habitats, marked with paint markers for identification purposes, and released at the center of each plant tray. Pitfalls were placed in a grid pattern throughout the cages for ground beetle recapture data. Their locations were determined using a labeled coordinate system for each pitfall. Pitfall locations were recorded twice a day over a 2-week period. To assess predation rates, moth egg cards were placed at eight locations in each tray for a 48-hour period and the number of removed eggs was counted. We hypothesize that ground beetle movement and foraging will be higher in the grass monoculture when compared to the corn and soybean monoculture. For the mixed plant trays, we expect the ground beetles to have higher predation rates and cross over into the grass habitats. Results from this study will give information on ground beetle movement and predation activity between agricultural crops and perennial grass habitats and can be useful for cultural control practices, such as prairie strips and diversified plantings, for pest management in agricultural systems.
Keywords: ground beetle; Carabidae; agro-ecology; pest management; cultural control; USDA NIFA 2019-67032-29071